A broadband dual-sense circularly polarized antenna - Lertsakwimam, Kittima; Phongcharoenpanich, Chuwong; Fukusako, Takeshi (My University, 2017)
A dual-sense circularly polarized antenna is proposed with a broadband 3-dB AR characteristics. The antenna consists of circular ring, four straight probes, which are place in along diameter direction of ring, four straight bars, and a reflector. The antenna is excited by the four straight probes to obtain both right hand circular polarization (RHCP) and left hand circular polarization (LHCP). The antenna has a 10dB-retum loss from 1.1 GHz-2.2 GHz, and the 3dB Axial Ratio (AR) bandwidth is from 1.2 GHz-2.1 GHz (the relative bandwidth is 54.5 %) and more than -30dB-level of isolation in frequency range of 1.4-1.7 GHz. The antenna element broadside gain is approximately 9.5 dBic at 1.7 GHz.
Keywords: Circularly polarized; Dual-sense; Ring antenna